Treatment of superficial basal cell carcinoma with ingenol mebutate gel, 0.05% - Bettencourt MS (Dove Medical Press, 2016)
Miriam S Bettencourt1,2 1Advanced Dermatology and Cosmetic Surgery, Henderson, 2Department of Dermatology, University of Nevada, Las Vegas, NV, USA Background: Basal cell carcinoma (BCC) is the most common cancer in Caucasians. Surgical approaches are the most widely used and effective treatment strategies for well-defined BCC. However, for patients with low-risk, superficial BCCs (sBCCs), medical therapy may be a treatment option. In this small case series, we describe our experience in using topical treatment with ingenol mebutate gel, 0.05%, for patients who refused surgical treatment for sBCC. Methods: We conducted a retrospective chart review of seven patients from our community dermatology practice for whom sBCC was treated with ingenol mebutate. The chart review extracted information on demography, dermatologic history, and prior treatment for actinic keratosis or skin cancer. Summary of the treatment outcome with ingenol mebutate included the size and location of the sBCCs, description of administration, local skin reactions, adverse events, and efficacy. Results: Histopathologic analysis of a shave biopsy sample of suspicious lesions on the trunk confirmed nine sBCCs: a single sBCC in five patients and two well-separated lesions in each of the other two patients. Patients were treated at 10 to 14 days after shave biopsy; biopsy sites were not required to be fully healed. Lesions were either occluded using a standard adhesive bandage (n=6) or not occluded (n=3). All patients experienced local skin reactions that began on day 1 or 2 of treatment, peaked on days 2 to 7, and were largely resolved at 2 weeks. All sBCCs were clinically resolved on short-term follow-up at 2 to 4 weeks. Repeat biopsy of six lesion sites in four patients at 3 or 4 months confirmed histologic clearance. There were no clinically suspicious lesions in any patients at subsequent follow-up evaluations at 3-month intervals. The longest follow-up to date has been 14 months. Conclusion: Ingenol mebutate gel, 0.05%, was efficacious and well tolerated for the treatment of biopsy-confirmed sBCCs on the trunk in seven patients. Keywords: superficial basal cell carcinoma, ingenol mebutate, nonsurgical treatment, local skin reaction